High plasticity nickel-based alloy pipe and method for manufacturing the same
Patent Information
- Application Number
- CN202611187178.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-08-06
AI Technical Summary
[0003]现有UNS N04400镍铜合金无缝管材制造通常重视冷加工、退火、尺寸控制和表面缺陷消除,但在退火软化、终道次变形与酸洗钝化之间缺少面向表面Cu/Ni原子比控制状态的协同控制
1.通过将再结晶退火与终道次小变形冷拔或冷整径相结合,管材在形成6-8级平均晶粒度的同时保留适度形变调节作用,使断后伸长率、抗拉强度和扩口性能之间形成更稳定的匹配关系,较单纯退火或单纯冷加工路线更有利于后续成形和装配。
Smart Images

Figure CN122688347B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nickel-based alloy seamless pipe manufacturing, specifically to a high-plasticity nickel-based alloy pipe and its manufacturing method. Background Technology
[0002] UNS N04400 nickel-copper alloy seamless tubing combines the corrosion resistance of nickel-based alloys with the surface stabilization properties of copper. It is commonly used in applications such as chemical media transportation, marine engineering heat exchange, corrosion-resistant equipment connections, and precision piping. In these applications, the tubing not only needs to maintain sufficient strength and dimensional stability but also requires high formability to meet subsequent processing requirements such as flaring, bending, assembly, and sealing. Furthermore, the chemical state and surface quality of the tubing's inner and outer surfaces directly affect the passivation state, media contact stability, and the reliability of sealing components during the initial service life. Therefore, establishing a manufacturing route for nickel-copper alloy seamless tubing that considers grain structure, final-pass deformation, surface Cu / Ni atomic ratio control, pickling and passivation, and roughness control is crucial for improving the batch consistency, forming applicability, and engineering service stability of corrosion-resistant tubing.
[0003] Existing manufacturing practices for UNS N04400 nickel-copper alloy seamless tubes typically emphasize cold working, annealing, dimensional control, and surface defect elimination. However, they lack synergistic control over the Cu / Ni atomic ratio state at the surface level during annealing softening, final-pass deformation, and pickling passivation. Chinese patent CN119387343A discloses a method for manufacturing small-diameter nickel-copper alloy seamless heat exchange tubes. Its background section points out that N04400 nickel-copper alloy seamless heat exchange tubes suffer from problems such as long manufacturing cycles, low first-pass yield, low production success rate, low dimensional accuracy, and poor internal and external surface quality. ASTM B165-26 also covers UNS N04400 cold-worked seamless tubes and tubing, requiring compliance with composition and tensile requirements. However, these disclosures or standards tend to focus more on manufacturing processes, dimensions, and basic mechanical quality requirements, without establishing a clear control logic for the bidirectional constraints between the Cu / Ni surface ratio, roughness, and forming plasticity during post-annealing surface treatment. Summary of the Invention
[0004] The purpose of this invention is to provide a high-plasticity nickel-based alloy pipe and its preparation method, which solves the problem that it is difficult to simultaneously achieve plasticity control, surface Cu / Ni atomic ratio control, roughness control, and surface Cu / Ni atomic ratio stability under humid and hot conditions in the current UNSN04400 nickel-copper alloy pipe.
[0005] Existing annealing and small deformation control are beneficial for forming plasticity but can easily alter the surface element retention state during subsequent pickling and passivation. Intensifying pickling and passivation may increase surface disturbance and affect plasticity performance. This invention achieves a balance between microstructure adjustment and surface treatment by controlling the sequence of recrystallization annealing, final small deformation, Cu / Ni ratio control, and nitric acid passivation. This balances forming plasticity, surface Cu / Ni atomic ratio control, roughness, and surface Cu / Ni atomic ratio stability under humid and hot conditions.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A high-plasticity nickel-based alloy pipe, wherein the pipe is a seamless UNS N04400 nickel-copper alloy pipe, comprising a UNS N04400 nickel-copper alloy matrix and a surface Cu / Ni atomic ratio controlled structure located on the inner and outer surfaces of the UNS N04400 nickel-copper alloy matrix. The controlled Cu / Ni atomic ratio structure satisfies that the surface Cu retention index R of the inner and outer surfaces is 0.80-1.20. The surface Cu retention index R is defined as the ratio of the Cu / Ni atomic ratio of the pipe surface to the Cu / Ni atomic ratio of the pipe matrix. The average grain size of the pipe is grade 6-8, the elongation at room temperature after fracture (A) is 45.0-55.0%, the outer surface roughness (Ra) is 0.20-1.60 μm, and the flaring rate is 15.0-25.0%.
[0007] Furthermore, based on the total mass of the pipe material as 100wt%, the UNS N04400 nickel-copper alloy matrix comprises: nickel, which is the balance after deducting copper, manganese, iron, silicon, carbon, sulfur, and unavoidable impurities, and its content is 63.00-69.00wt%; copper, with a content of 28.00-34.00wt%; manganese, with a content of 0.20-2.00wt%; iron, with a content of 0.10-2.50wt%; silicon, with a content of 0.02-0.50wt%; carbon, with a content of 0.005-0.300wt%; sulfur, with a content of 0.0005-0.024wt%; the total amount of unavoidable impurities does not exceed 0.50wt%, and the sum of all components is 100wt%.
[0008] Furthermore, the surface Cu / Ni atomic ratio controlled structure is formed through a Cu / Ni ratio controlled acid pickling step, which includes the following steps: A1. Provide the annealed seamless tubing of the UNS N04400 nickel-copper alloy; A2. Prepare an acid washing solution, wherein the acid washing solution is selected from any one of a first acid washing solution, a second acid washing solution, and a third acid washing solution, wherein the first acid washing solution is prepared by hydrofluoric acid and deionized water, the second acid washing solution is prepared by hydrochloric acid, copper sulfate pentahydrate, and deionized water, and the third acid washing solution is prepared by sulfuric acid, copper sulfate pentahydrate, and deionized water; A3. Place the pipe in the pickling solution and treat it for 0.5-15.0 min under normal pressure, temperature of 15-40℃, and pH value not higher than 2; A4. Pickling shall be terminated when the residual oxide scale area on the surface of the pipe is 0-2.0% and the pickling weight loss is 0.20-3.00 g / m². A5. Rinse with deionized water until the pH of the final rinse water is 6-8, and dry at 60-120℃ for 5-30 minutes; A6. The surface Cu retention index R of the obtained pipe is 0.80-1.20.
[0009] Furthermore, the surface Cu / Ni atomic ratio controlled structure is also formed through a nitric acid passivation step, which includes the following steps: B1. The pipe treated by the Cu / Ni ratio controlled pickling step is placed in a nitric acid aqueous solution, which is prepared by nitric acid and deionized water; B2. Passivate for 1.0-15.0 min under normal pressure, temperature of 15-40℃, and pH value not higher than 2; B3. Rinse with deionized water until the pH of the final rinse water is 6-8; B4. Dry at 60-120℃ for 5-30 minutes; B5. The surface roughness Ra of the resulting pipe is 0.20-1.60 μm, and the surface Cu retention index R is 0.80-1.20.
[0010] Furthermore, the UNS N04400 nickel-copper alloy matrix is formed by recrystallization annealing and final minor deformation cold working, specifically including: C1. Anneal the cold-worked UNS N04400 nickel-copper alloy tubing at a temperature of 760-880℃ and a holding time of 10-60 minutes. C2. The annealing is carried out in a nitrogen or argon atmosphere, or the annealing is carried out in an air atmosphere followed by pickling with Cu / Ni ratio control. C3. After annealing, perform final minor deformation cold drawing or cold straightening, wherein the cross-sectional reduction rate of the final minor deformation cold drawing or cold straightening is 2.00-6.00%; C4. After the final small deformation cold drawing or cold straightening, the average grain size of the obtained pipe is grade 6-8, and the room temperature elongation after fracture A is 45.0-55.0%.
[0011] Furthermore, the outer diameter of the pipe is 6.0-168.0 mm, the wall thickness is 0.50-12.00 mm, the ellipticity is 0-1.50%, the wall thickness deviation is 0-10.00%, and there are no visible cracks, folds, or delaminations on the inner and outer surfaces. Moreover, there are no cracks or delaminations at the bent parts of the pipe after it has been flattened.
[0012] Furthermore, the room temperature tensile strength Rm of the pipe is 520-580MPa, the specified plastic elongation strength Rp0.2 is 280-350MPa, and the Rockwell hardness HRB is 75-85.
[0013] Furthermore, in the pipe, the inter-batch or intra-batch coefficient of variation of elongation after fracture A is 0-8.0%, the intra-batch coefficient of variation of surface Cu retention index R is 0-10.0%, and the intra-batch coefficient of variation of outer surface roughness Ra is 0-15.0%.
[0014] As a concept of this invention, the present invention employs a controlled Cu / Ni atomic ratio structure and controlled grain microstructure on the surface of a UNS N04400 nickel-copper alloy matrix. This is primarily used to achieve a synergistic balance between forming plasticity and surface Cu / Ni atomic ratio control performance. In existing technologies, to improve the forming plasticity of pipes, annealing is typically used to soften the microstructure or reduce the final deformation strength. However, microstructure softening and changes in oxide scale state make subsequent surface treatments more difficult to maintain the Cu / Ni surface ratio. Furthermore, to improve the surface Cu / Ni atomic ratio control performance, pickling and passivation intensity are usually adjusted, but this may negatively weaken the flaring and surface quality due to surface dissolution, roughening, or local disturbances. This invention, by limiting the average grain size, elongation after fracture, external surface roughness, flaring ratio, and surface Cu retention index to a mutually matched state, establishes a balance between matrix microstructure control and surface treatment, thereby balancing mutually restrictive performance. When the surface Cu retention index R is greater than 1.0, it indicates that the final surface Cu / Ni atomic ratio is higher than the matrix Cu / Ni atomic ratio. The formation of the R value includes the preferential dissolution of Ni during pickling and the surface exchange or deposition process involving Cu ions in the pickling system containing copper sulfate pentahydrate. This invention uses the R value of the inner and outer surfaces of the final pipe as a quality control index for the controlled state of the surface Cu / Ni atomic ratio.
[0015] This invention also discloses a method for preparing a high-ductility nickel-based alloy pipe, comprising the following steps: S1. Provide UNS N04400 nickel-copper alloy tube blanks; S2. The UNS N04400 nickel-copper alloy tube blank is cold rolled and / or cold drawn to form a cold-worked tube; S3. Anneal the cold-worked pipe at a temperature of 760-880℃ and a holding time of 10-60 minutes. S4. Perform final small-deformation cold drawing or cold straightening on the annealed pipe, with a cross-sectional reduction rate of 2.00-6.00%; S5. Perform mechanical pre-cleaning on the pipe after step S4, and then perform Cu / Ni ratio controlled pickling on the pre-cleaned pipe to remove oxide scale and form a surface Cu / Ni atomic ratio controlled structure. S6. Passivate the pipe after step S5 with nitric acid to form a passivated surface; S7. Clean, dry, straighten and cut to length to obtain the high-plasticity nickel-based alloy pipe.
[0016] Furthermore, in step S2, the total cross-sectional reduction rate of the cold rolling and / or cold drawing is 35.00-75.00%, and the single-pass cross-sectional reduction rate is 8.00-30.00%; in step S4, the final pass of small deformation cold drawing or cold straightening is not subjected to recrystallization annealing at a temperature higher than 700°C.
[0017] Furthermore, the mechanical pre-cleaning is applied to the inner and outer surfaces of the pipe after step S4, reducing the oxide scale thickness by 30.0-90.0% and reducing the pickling time in step S5 by 20.0-70.0%; the reduction in pickling time is calculated based on the pickling time required to reach the same pickling termination criterion without mechanical pre-cleaning.
[0018] Furthermore, the pipes obtained after steps S5 and S6 simultaneously meet the following requirements: surface Cu retention index R is 0.80-1.20, outer surface roughness Ra is 0.20-1.60μm, and pickling weight loss is 0.20-3.00g / m².
[0019] Furthermore, in the Cu / Ni ratio controlled pickling step, the pickling aqueous solution is selected from any one of the first pickling aqueous solution, the second pickling aqueous solution, and the third pickling aqueous solution; the first pickling aqueous solution is prepared by hydrofluoric acid and deionized water, with a hydrogen fluoride content of 8.00-30.00 wt%; the second pickling aqueous solution is prepared by hydrochloric acid, copper sulfate pentahydrate, and deionized water, with a hydrogen chloride content of 5.00-15.00 wt% and a copper sulfate pentahydrate content of 20-100 g / L; the third pickling aqueous solution is prepared by sulfuric acid, copper sulfate pentahydrate, and deionized water, with a sulfuric acid content of 8.00-20.00 wt% and a copper sulfate pentahydrate content of 20-100 g / L; the obtained pickling aqueous solution is used to pickle UNS N04400 nickel-copper alloy seamless pipes after annealing and final small deformation cold working, and after pickling, the oxide scale is removed from the pickled pipes, which are then subjected to cleaning or nitric acid passivation steps.
[0020] Furthermore, the UNS N04400 nickel-copper alloy seamless pipe, after annealing and final minor deformation cold working, is placed in an acid pickling solution, ensuring that both the inner and outer surfaces of the pipe are in contact with the solution. The treatment is carried out for 0.5-15.0 minutes under normal pressure, at a temperature of 15-40℃, and with a pH value not exceeding 2. Acid pickling is stopped when the residual oxide scale area on the pipe surface is 0-2.0% and the pickling weight loss is 0.20-3.00 g / m². The resulting acid-piped pipe is then rinsed with deionized water until the final rinse water pH reaches 6-8, and dried at 60-120℃ for 5-30 minutes.
[0021] Furthermore, the residual oxide scale area ratio is obtained by acquiring images of the inner and outer surfaces of the pickled pipes and calculating the proportion of the residual oxide scale area to the total surface area of the tested surface. Within the same batch of tests, image acquisition is conducted under the same light source, the same acquisition magnification, and the same exposure conditions. The oxide scale area is identified according to the same grayscale binarization threshold rule. After acquiring test images of the inner and outer surfaces respectively, the residual oxide scale area ratio is calculated based on the tested area. The pickling weight loss is the difference between the mass of the dried pipe before pickling and the mass of the pipe after pickling, cleaning, and drying, divided by the sum of the inner and outer surface areas of the pipes involved in pickling, in g / m². The residual oxide scale area ratio and the pickling weight loss are used as pickling termination criteria.
[0022] Furthermore, in the nitric acid passivation step, the nitric acid aqueous solution is prepared by mixing nitric acid and deionized water, with a nitric acid content of 10.00-25.00 wt%. The pipe, after being acid-washed and cleaned with a controlled Cu / Ni ratio, is placed in the nitric acid aqueous solution and passivated for 1.0-15.0 min under normal pressure, a temperature of 15-40℃, and a pH value not higher than 2. The passivated pipe is then rinsed with deionized water until the pH of the final rinse water is 6-8, and dried at 60-120℃ for 5-30 min to obtain a pipe with a passivated surface.
[0023] Furthermore, the samples used for determining the surface Cu retention index R were final-state pipes after undergoing pickling, nitric acid passivation, cleaning, and drying with controlled Cu / Ni ratios. The surface Cu / Ni atomic ratio of the pipes was determined using X-ray photoelectron spectroscopy according to GB / T19500-2025, with the energy scale calibrated according to GB / T22571-2017. The test surfaces included the outer surface of the pipes and the inner surface exposed after axial sectioning. The peak areas of Cu2p and Ni2p characteristic peaks were recorded and corrected to atomic percentages according to the corresponding sensitivity factors before calculating the Cu / Ni atomic ratio. The substrate Cu / Ni atomic ratio of the pipes was determined using inductively coupled plasma atomic emission spectrometry on samples taken from the middle of the pipe wall and dissolved. The surface Cu retention index R is the ratio of the surface Cu / Ni atomic ratio to the substrate Cu / Ni atomic ratio. R was calculated for both the inner and outer surfaces and used as quality control data for the final-state pipe surface Cu / Ni atomic ratio controlled structure.
[0024] Furthermore, the average grain size was measured by sampling the cross-section of the pipe wall in the final state; the room temperature elongation after fracture A was the elongation after fracture measured at room temperature for a tensile specimen with a gauge length L0 of 50 mm; the flaring ratio was determined by performing a flaring test on the end of the final state pipe using a conical core with a cone angle of 60°, and calculated by dividing the difference between the maximum outer diameter after flaring and the outer diameter before flaring by the outer diameter before flaring; the outer surface roughness Ra was measured axially on the outer surface of the final state pipe, and the obtained data was used to determine whether the final state pipe simultaneously met the parameters of grain size, plasticity, flaring, and surface roughness.
[0025] Furthermore, the same batch consists of pipes from the same furnace number, the same annealing batch, the same final small deformation cold working batch, and the same pickling and passivation batch; the intra-batch coefficient of variation is the percentage obtained by dividing the standard deviation of the corresponding parameters of each sampled pipe within the same batch by the arithmetic mean and then multiplying by 100%; the inter-batch coefficient of variation is the percentage obtained by dividing the standard deviation of the batch average values of the corresponding parameters of different batches of pipes by the arithmetic mean of the average values of each batch and then multiplying by 100%; the coefficients of variation for elongation after fracture (A), surface Cu retention index (R), and external surface roughness (Ra) are calculated according to the above-mentioned calibers. The rate of change of R after wet heating is calculated based on the relative change of R value of the same surface before and after wet heating, and the calculation formula is: Rate of change of R after wet heating = |R after wet heating - R before wet heating| / R before wet heating × 100%.
[0026] Furthermore, before the Cu / Ni ratio controlled pickling step, the pipes after the final small deformation cold drawing or cold sizing are subjected to mechanical pre-cleaning. The mechanical pre-cleaning acts on the oxide scale layer on the inner and outer surfaces of the pipes, and the ratio of the difference in oxide scale thickness before and after mechanical pre-cleaning to the oxide scale thickness before mechanical pre-cleaning is used as the oxide scale thickness reduction ratio. When the oxide scale thickness reduction ratio is 30.0-90.0%, the mechanically pre-cleaned pipes are sent to the Cu / Ni ratio controlled pickling step.
[0027] As another aspect of this invention, the present invention employs a sequential process of cold rolling and / or cold drawing, recrystallization annealing, final pass small deformation cold drawing or cold straightening, Cu / Ni ratio controlled pickling, and nitric acid passivation. This is primarily used to achieve, fix, or amplify the aforementioned synergistic effects. Existing technologies, while improving the softening degree of annealing alone is beneficial for plastic recovery, easily makes subsequent surface deoxidation treatment more reliant on intensified pickling, thus increasing surface condition fluctuations. While intensified pickling and passivation alone is beneficial for removing oxide scale and forming a passivated surface, it may increase roughness and the risk of selective dissolution of the metal surface. This invention, by setting a final pass small deformation after annealing and establishing a sequential connection between mechanical pre-cleaning, Cu / Ni ratio controlled pickling, and nitric acid passivation, ensures that structural stability, surface Cu / Ni atomic ratio control, and roughness control are mutually coordinated in a continuous process, thereby maintaining consistent product performance in batch production.
[0028] Recrystallization annealing and final small deformation cold drawing or cold heading mainly correspond to microstructure softening and final dimensional deformation control, respectively. The former is beneficial for restoring plasticity, but when used alone, it can easily lead to the grain state and surface oxide scale state being more sensitive to subsequent processing. The latter is beneficial for improving dimensional consistency and surface shaping, but if its proportion is too high, it will increase work hardening and sacrifice elongation after fracture. Cu / Ni ratio control pickling and nitric acid passivation mainly correspond to oxide scale removal and surface stabilization, respectively. Pickling alone increases the risk of surface dissolution and roughening, while relying solely on passivation makes it difficult to eliminate the interference of annealed oxide scale on the Cu / Ni surface ratio. This invention achieves mutual correction between microstructure control and surface treatment by sequentially matching the deformation ratio, annealing window, pickling termination criterion, and passivation conditions, ultimately taking into account forming plasticity, surface Cu / Ni atomic ratio control, roughness, and surface Cu / Ni atomic ratio stability under humid and hot conditions.
[0029] Beneficial technical effects 1. By combining recrystallization annealing with final small deformation cold drawing or cold sizing, the pipe retains a moderate deformation adjustment effect while forming an average grain size of 6-8 grades, so that the elongation after fracture, tensile strength and flaring performance form a more stable matching relationship, which is more conducive to subsequent forming and assembly than simple annealing or simple cold working route.
[0030] 2. By controlling the type of pickling solution, treatment time, temperature, pH, residual oxide scale area ratio, and pickling weight loss through Cu / Ni ratio control, the removal of oxide scale during annealing and the maintenance of surface Cu / Ni atomic ratio are simultaneously constrained, reducing the risk of surface element deviation and roughening caused by excessive pickling, and facilitating the formation of a surface Cu / Ni atomic ratio controlled structure with consistent inner and outer surfaces.
[0031] 3. By controlling the Cu / Ni ratio and then performing nitric acid passivation, and controlling the nitric acid content, passivation time, cleaning pH and drying conditions, the passivated surface is formed within a low external surface roughness range. This avoids increasing surface disturbance by relying solely on strengthening surface treatment to pursue stability. It is beneficial to balance the surface Cu / Ni atomic ratio stability under humid and hot conditions with the subsequent sealing contact quality.
[0032] 4. By setting quality control standards such as mechanical pre-cleaning, oxide scale residual area ratio, pickling weight loss, surface Cu retention index R, and intra- or inter-batch variation coefficient, a closed-loop control is formed for pipes from cold working, annealing, pickling, passivation to final state inspection. This is more conducive to batch consistency and repeatable manufacturing than processes that only use appearance qualification as the endpoint. Attached Figure Description
[0033] Figure 1 This diagram illustrates the effect of the reduction rate of the final small deformation cold straightening section on the elongation after fracture (A) and the surface Cu retention index (R) of the outer surface.
[0034] Figure 2 This diagram shows the effect of annealing temperature on the elongation after fracture (A) and the surface Cu retention index (R) of the outer surface.
[0035] Figure 3 This diagram illustrates the effect of pickling time on the Cu retention index R on the outer surface and the ratio of residual oxide scale area.
[0036] Figure 4 This diagram shows the effect of nitric acid content on the surface Cu retention index R on the outer surface and the rate of change of R after humid heat.
[0037] Figure 5 This diagram illustrates the effect of the mechanical pre-cleaning ratio on the surface Cu retention index R and the surface roughness Ra of the proposed scheme.
[0038] Figure 6 The graph shows the grain size difference distribution curves for Example 1, Comparative Example 1, and Comparative Example 2.
[0039] Figure 7 The cumulative grain size distribution curves for Example 1, Comparative Example 1, and Comparative Example 2 are shown.
[0040] Figure 8 The graphs show the EBSD orientation difference distribution curves for Example 1, Comparative Example 1, and Comparative Example 2.
[0041] Figure 9 The table shows the room temperature engineering stress-strain curves for Example 1, Comparative Example 1, and Comparative Example 9.
[0042] Figure 10 This is a scatter plot of the mean and standard deviation of the flaring rate for Example 1, Comparative Example 1, and Comparative Example 9.
[0043] Figure 11 The above are the XPS Cu2p / Ni2p peak superposition spectra of Example 1, Comparative Example 10, and Comparative Example 11.
[0044] Figure 12 The image shows a comparison of the surface Cu retention index R of Example 1, Comparative Example 10, and Comparative Example 11.
[0045] Figure 13 The graph shows the change rate of surface roughness Ra and R after humid heat in Examples 1, 6, and 8.
[0046] Figure 14 The graph shows the ratio of residual oxide scale area to pickling weight loss in Examples 1, 5, and 7, plotted on a dual Y-axis.
[0047] Figure 15 The images show a comparison of the SEM morphology of the final product of Example 1 and the final product of Comparative Example 6; where a is a medium-magnification SEM image of the final product of Example 1; b is a medium-magnification SEM image of the final product of Comparative Example 6; c is a high-magnification SEM image of the final product of Example 1; and d is a high-magnification SEM image of the final product of Comparative Example 6.
[0048] Figure 16 The images show a comparison of the TEM structures of the final product of Example 1 and the final product of Comparative Example 6; where a is a bright-field TEM image of the final product of Example 1; b is a bright-field TEM image of the final product of Comparative Example 6; c is an HRTEM image of the final product of Example 1; d is an HRTEM image of the final product of Comparative Example 6; e is an EDS surface scan of the final product of Example 1; and f is an EDS surface scan of the final product of Comparative Example 6. Detailed Implementation
[0049] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.
[0050] Example 1 I. Preparation Object and Raw Material Condition: Ten seamless tubes were prepared using UNS N04400 nickel-copper alloy tube blanks from the same heat number. The finished product had an outer diameter of 6.0 mm and a wall thickness of 0.50 mm. The UNS N04400 nickel-copper alloy matrix, based on a total mass of 100 wt%, consisted of 28.00 wt% copper, 0.20 wt% manganese, 2.50 wt% iron, 0.02 wt% silicon, 0.005 wt% carbon, 0.0005 wt% sulfur, and 0.3045 wt% unavoidable impurities. The remaining nickel content after deducting the above components was calculated to be 68.97 wt%. The raw material was a commercially available corrosion-resistant nickel-copper alloy tube blank. All acid solutions were analytical grade or industrial pickling grade, and the conductivity of deionized water was no greater than 5 μS / cm.
[0051] II. Cold Working and Annealing: UNS N04400 nickel-copper alloy tube blanks were cold rolled and cold drawn to form cold-worked tubes with a total cross-sectional reduction rate of 35.00% and a single-pass cross-sectional reduction rate of 8.00%. The cold-worked tubes were placed in a nitrogen atmosphere annealing furnace with nitrogen purity ≥99.9%. The temperature was increased to 760℃ at 10℃ / min under normal pressure and held for 60 min. Subsequently, the tubes were cooled to below 80℃ under nitrogen protection before being removed from the furnace. After annealing, the oxide scale on the tube surface was continuous but thin, and no visible cracks, folds, or delaminations were observed in the tube body.
[0052] III. Final Small Deformation Treatment: The annealed pipe undergoes a final small deformation cold sizing process with a cross-sectional reduction rate of 2.00%, a sizing speed of 3 m / min, a sizing die inlet cone angle of 12°, and commercially available chlorine-free drawing lubricant. No recrystallization annealing above 700°C is performed after sizing. After cold sizing, the pipe is cleaned with 40°C deionized water and a neutral detergent for 10 minutes, and then dried with compressed air until no visible water marks remain on the surface.
[0053] IV. Mechanical Pre-cleaning and Cu / Ni Ratio Controlled Pickling: The inner and outer surfaces of the cold-sizing pipes were mechanically pre-cleaned with a nylon brush at 600 rpm for 2 minutes, resulting in a 30.0% reduction in oxide scale thickness and a 20.0% reduction in pickling time. A first pickling solution was prepared with 8.00 wt% hydrogen fluoride and the remainder being deionized water. The pipes were completely immersed in the first pickling solution, ensuring both the inner and outer surfaces were in contact with the solution, and treated for 0.5 minutes at atmospheric pressure, 15°C, and pH 2.0. After removal, images were acquired. The residual oxide scale area was 2.0%, and the pickling weight loss was 0.20 g / m². Once the pickling termination criteria were met, the cleaning process immediately commenced. The pipes were rinsed with deionized water until the final rinse water pH reached 6, and then dried at 60°C for 5 minutes.
[0054] V. Nitric Acid Passivation and Final Finishing: Prepare a nitric acid aqueous solution with a nitric acid content of 10.00 wt%, the remainder being deionized water. Immerse the pickled and dried pipes in the nitric acid aqueous solution and passivate for 1.0 min at atmospheric pressure, 15℃, and pH 2.0. After passivation, rinse with deionized water until the final rinse water pH reaches 6, then dry at 60℃ for 5 min. Subsequently, straighten and cut to length at a straightening speed of 4 m / min, a cutting length of 1000 mm, ovality of 0%, and wall thickness deviation of 0%.
[0055] VI. Quality Inspection Methods and Results: Samples were taken from the final state of the pipe. The average grain size was measured to be grade 6 using metallographic methods. The gauge length L0 of the room temperature tensile specimens was 50 mm. The room temperature elongation after fracture A was 45.0%, the room temperature tensile strength Rm was 520 MPa, the specified plastic extension strength Rp0.2 was 280 MPa, and the Rockwell hardness HRB was 75. A flaring test was conducted using a 60° conical mandrel, with a flaring rate of 15.0%. The surface roughness Ra of the outer surface was measured to be 1.60 μm using the contour method. The surface Cu retention index R of the inner surface and the outer surface was measured to be 0.80 using X-ray photoelectron spectroscopy. No cracks or delamination were found in the bent parts after flattening. The intra-batch coefficient of variation for elongation after fracture A was 1.78%, the intra-batch coefficient of variation for surface Cu retention index R was 2.50%, and the intra-batch coefficient of variation for surface roughness Ra was 5.00%.
[0056] VII. Features and application scenarios of this embodiment: This embodiment adopts relatively conservative cold working and pickling passivation conditions, the pipe specifications are relatively small, the proportion of small deformation in the final pass is relatively low, and the surface treatment intensity is relatively mild. It is suitable for corrosion-resistant pipe preparation scenarios that require small outer diameter, thin wall size and mild surface treatment window.
[0057] Example 2 Raw materials and product specifications: This embodiment prepares 6 seamless UNS N04400 nickel-copper alloy tubes with an outer diameter of 168.0 mm and a wall thickness of 12.00 mm. The UNS N04400 nickel-copper alloy matrix, based on a total mass of 100 wt%, contains 34.00 wt% copper, 2.00 wt% manganese, 0.10 wt% iron, 0.50 wt% silicon, 0.300 wt% carbon, 0.024 wt% sulfur, and 0.076 wt% unavoidable impurities. Nickel is the balance after deducting the above components, with a content of 63.00 wt%. The tube blank is a commercially available corrosion-resistant nickel-copper alloy tube blank, and the pickling and passivation chemicals are commercially available analytical grade or industrial pickling grade chemicals.
[0058] Cold rolling, cold drawing, and heat treatment process: UNS N04400 nickel-copper alloy tube blanks are cold rolled and cold drawn, with a total cross-sectional reduction rate of 75.00% and a single-pass cross-sectional reduction rate of 30.00%, forming cold-worked tubes. The cold-worked tubes are placed in an argon atmosphere furnace with argon purity ≥99.9%, heated to 880℃ at atmospheric pressure at a rate of 8℃ / min, held for 10 minutes, and then cooled in the furnace to 120℃ before being removed. After annealing, the tube surface has a uniform oxide scale, and there are no visible cracks, folds, or delaminations on the inner and outer surfaces.
[0059] Final small deformation cold drawing: After annealing, the tube undergoes cold drawing with a cross-sectional reduction rate of 6.00% at a drawing speed of 1.5 m / min. Before cold drawing, the inner and outer surfaces are coated with a commercially available chlorine-free drawing lubricant. After cold drawing, the tube is cleaned with deionized water and a neutral cleaning agent at 45°C for 12 minutes, followed by blowing with compressed air until the inner and outer surfaces are dry. No recrystallization annealing above 700°C is performed after the final small deformation cold drawing.
[0060] Mechanical pre-cleaning, pickling, and rinsing: A flexible abrasive brush was used to mechanically pre-clean the inner and outer surfaces of the pipe at 1000 rpm for 6 minutes, resulting in a 90.0% reduction in oxide scale thickness and a 70.0% reduction in pickling time. A first pickling solution was prepared with 30.00 wt% hydrogen fluoride and the remainder deionized water. The pipe was placed in the pickling tank and treated for 15.0 minutes at atmospheric pressure, 40°C, and pH 0.8, ensuring both the inner and outer surfaces were thoroughly wetted with the pickling solution. Image analysis after pickling showed a 0% residual oxide scale area and a pickling weight loss of 3.00 g / m². The pipe was then rinsed with deionized water until the final rinse water pH reached 8, and dried at 120°C for 30 minutes.
[0061] Nitric acid passivation and finished product finishing: Prepare a nitric acid aqueous solution with a nitric acid content of 25.00 wt%, the balance being deionized water. Place the pickled and dried pipes in the nitric acid aqueous solution and passivate for 15.0 min at normal pressure, 40℃, and pH 0.8. After passivation, rinse with deionized water until the final rinse water pH is 8, and dry at 120℃ for 30 min. After drying, straighten and cut to length at a straightening speed of 1 m / min, achieving a finished product ovality of 1.50% and a wall thickness deviation of 10.00%.
[0062] Quality Inspection Methods and Results: Metallographic examination of the pipe wall section in the final state showed an average grain size of grade 8; the gauge length L0 of the room temperature tensile specimen was 50 mm, and the measured room temperature elongation after fracture A was 55.0%, the room temperature tensile strength Rm was 580 MPa, the specified plastic extension strength Rp0.2 was 350 MPa, and the Rockwell hardness HRB was 85; the flaring ratio was 25.0%; the outer surface roughness Ra was 0.20 μm; X-ray photoelectron spectroscopy and matrix composition analysis calculated the inner surface Cu retention index R to be 1.20, and the outer surface Cu retention index R was also 1.20; no cracks or delamination were found in the bent portion after flattening. The intra-batch coefficient of variation for elongation after fracture A was 1.27%, the intra-batch coefficient of variation for the surface Cu retention index R was 2.50%, and the intra-batch coefficient of variation for the outer surface roughness Ra was 15.00%.
[0063] The features of this embodiment are: it adopts higher cold working compression, higher annealing temperature, higher final pass small deformation ratio and stronger surface treatment conditions, which is suitable for the preparation of UNS N04400 nickel-copper alloy seamless tubes with larger outer diameter and thick wall, and demonstrates feasibility under a wider process window.
[0064] Example 3 In this embodiment, eight medium-sized seamless tubes were prepared using UNS N04400 nickel-copper alloy billets from the same furnace. The finished products had an outer diameter of 60.0 mm, a wall thickness of 4.00 mm, an ellipticity of 0.80%, and a wall thickness deviation of 5.00%. The matrix contained 30.50 wt% copper, 1.10 wt% manganese, 1.30 wt% iron, 0.25 wt% silicon, 0.080 wt% carbon, 0.010 wt% sulfur, 0.20 wt% unavoidable impurities, and nickel as the balance, calculated to be 66.56 wt%.
[0065] The material is first cold-rolled and cold-drawn, with a total cross-sectional reduction rate of 55.00% and a single-pass cross-sectional reduction rate of 18.00%, forming a cold-worked tube. The cold-worked tube is then placed in an air atmosphere annealing furnace, heated to 820℃ at a rate of 9℃ / min, held for 30 min, and then air-cooled to room temperature. After air annealing, a continuous oxide scale forms on the tube surface. This scale is then removed and the surface condition is adjusted through subsequent pickling with a controlled Cu / Ni ratio.
[0066] After annealing, the pipes underwent a final small deformation cold sizing process with a cross-sectional reduction rate of 4.00% at a sizing speed of 2.5 m / min. Following sizing, the pipes were cleaned for 8 minutes with 45°C deionized water and a neutral cleaning agent, and then dried with compressed air. No recrystallization annealing above 700°C was performed after cold sizing. Subsequently, a composite nylon brush was used to mechanically pre-clean the inner and outer surfaces of the pipes at 800 rpm for 4 minutes, resulting in a 60.0% reduction in oxide scale thickness and a 45.0% reduction in pickling time.
[0067] In this embodiment, a second pickling solution was used, containing 5.00 wt% hydrogen chloride, 20 g / L copper sulfate pentahydrate, and the remainder deionized water. The pipe was immersed in the second pickling solution and treated for 6.0 min at normal pressure, 25°C, and pH 1.5. During the pickling process, the pipe was gently agitated every 2 min to promote uniform contact between the inner and outer surfaces. Images of the inner and outer surfaces were acquired after pickling, showing a residual oxide scale area of 0.8% and a pickling weight loss of 1.10 g / m². Subsequently, the pipe was rinsed with deionized water until the pH of the final rinse water reached 7, and then dried at 90°C for 15 min.
[0068] After pickling and drying, the pipes proceed to the nitric acid passivation step. The nitric acid aqueous solution contains 15.00 wt% nitric acid, with the remainder being deionized water. Passivation is carried out for 7.0 min at atmospheric pressure, 25°C, and pH 1.5. After passivation, the pipes are rinsed with deionized water until the pH of the final rinse water reaches 7, and then dried at 90°C for 15 min. Subsequently, straightening and length setting are performed, with a set length of 2000 mm.
[0069] The test results show that the average grain size of the final state pipe is grade 7, the elongation at room temperature after fracture (A) is 50.0%, the tensile strength at room temperature (Rm) is 550 MPa, the specified plastic extension strength (Rp0.2) is 315 MPa, and the Rockwell hardness (HRB) is 80. The flaring ratio measured using a 60° conical core is 20.0%. The outer surface roughness (Ra) is 0.85 μm. The inner surface Cu retention index (R) is 0.96, and the outer surface Cu retention index (R) is 0.98. The intra-batch coefficient of variation for elongation at fracture (A) is 1.20%, the intra-batch coefficient of variation for surface Cu retention index (R) is 2.04%, and the intra-batch coefficient of variation for outer surface roughness (Ra) is 5.88%. No cracks or delamination were found in the bent portion after flattening.
[0070] The applicable scenario for this embodiment: This embodiment adopts medium cold working compression, medium annealing and heat preservation, and pickling conditions of hydrochloric acid-copper sulfate pentahydrate system. It is suitable for medium-sized corrosion-resistant pipes that require surface element retention, uniform contact between inner and outer surfaces and batch stability.
[0071] Example 4 (1) Sample size and composition control: Twelve seamless UNS N04400 nickel-copper alloy tubes were prepared as follows: the finished product had an outer diameter of 25.4 mm, a wall thickness of 1.20 mm, an ellipticity of 0.30%, and a wall thickness deviation of 2.00%. The UNS N04400 nickel-copper alloy matrix, based on a total mass of 100 wt%, consisted of 32.00 wt% copper, 0.80 wt% manganese, 1.80 wt% iron, 0.35 wt% silicon, 0.150 wt% carbon, and 0.015 wt% sulfur. Unavoidable impurities were below the detection limit and were counted as 0 wt%. Nickel was the balance after deducting the above components, calculated to be 64.89 wt%. The tube blank was a commercially available corrosion-resistant nickel-copper alloy tube blank, and the pickling and passivation reagent was a commercially available analytical grade or industrial pickling grade.
[0072] (2) Cold working, annealing, and final small deformation: The tube blank was cold rolled and cold drawn, with a total cross-sectional reduction rate of 65.00% and a single-pass cross-sectional reduction rate of 25.00%. The resulting cold-worked tube was placed in an argon atmosphere annealing furnace with argon purity ≥99.9%, heated to 850℃ at atmospheric pressure at 10℃ / min, held for 20min, and then cooled to below 100℃ under argon protection. After annealing, the final small deformation cold drawing was performed, with a cross-sectional reduction rate of 5.00% and a cold drawing speed of 2m / min. After cold drawing, the tube was cleaned with deionized water and a neutral cleaning agent at 40℃ for 10min, dried, and then subjected to surface treatment.
[0073] (3) Mechanical pre-cleaning and Cu / Ni ratio controlled pickling: A flexible brush was used to mechanically pre-clean the inner and outer surfaces of the pipe at a speed of 900 rpm for 5 min. The oxide scale thickness was reduced by 75.0%, and the pickling time was reduced by 60.0%. In this embodiment, a third pickling aqueous solution was used, with a sulfuric acid content of 20.00 wt%, a copper sulfate pentahydrate content of 100 g / L, and the remainder being deionized water. The pipe was placed in the third pickling aqueous solution and treated for 10.0 min under normal pressure, 35°C, and pH 1.2. After pickling, the residual oxide scale area was 0.5%, and the pickling weight loss was 2.20 g / m². Subsequently, it was rinsed with deionized water until the pH of the final rinse water was 7, and then dried at 100°C for 20 min.
[0074] (4) Nitric acid passivation, cleaning, drying, and finishing: Prepare a nitric acid aqueous solution with a nitric acid content of 20.00 wt%. Place the pickled pipe into the nitric acid aqueous solution and passivate for 10.0 min at normal pressure, 35℃, and pH 1.2. After passivation, rinse with deionized water until the pH of the final rinse water is 7, and dry at 100℃ for 20 min. After drying, straighten and cut to length at a straightening speed of 3 m / min and a cutting length of 1500 mm. The final pipe has no visible cracks, folds, or delamination on its inner and outer surfaces.
[0075] (5) Quality inspection methods and results: The average grain size of the final state pipe is grade 7, the elongation after fracture at room temperature is 52.0%, the tensile strength at room temperature is 560 MPa, the specified plastic extension strength Rp0.2 is 330 MPa, the Rockwell hardness HRB is 82; the flaring rate is 22.0%; the outer surface roughness Ra is 0.60 μm; the inner surface Cu retention index R is 1.05, the outer surface Cu retention index R is 1.06; the intra-batch coefficient of variation of elongation after fracture A is 1.15%, the intra-batch coefficient of variation of surface Cu retention index R is 1.89%, and the intra-batch coefficient of variation of outer surface roughness Ra is 6.67%; there are no cracks or delamination in the bent part after flattening.
[0076] (6) Process characteristics and application direction of this embodiment: This embodiment adopts high cold working compression, high final pass small deformation ratio and sulfuric acid-copper sulfate pentahydrate system pickling conditions, taking into account the dimensional stability, surface element retention and surface quality control of small and medium-sized pipes, and is suitable for engineering pipelines that have requirements for forming connection and corrosion resistance.
[0077] Comparative Example 1: Basically the same as Example 1, except that the cross-sectional reduction rate of the final small deformation cold finishing is 1.00%, while other conditions remain at UNS. The N04400 nickel-copper alloy matrix contains 28.00 wt% copper, 0.20 wt% manganese, 2.50 wt% iron, 0.02 wt% silicon, 0.005 wt% carbon, 0.0005 wt% sulfur, 0.3045 wt% unavoidable impurities, and nickel as the balance. The finished product has an outer diameter of 6.0 mm, a wall thickness of 0.50 mm, a total cross-sectional reduction rate of 35.00%, a single-pass cross-sectional reduction rate of 8.00%, annealing at 760℃ for 60 min in a nitrogen atmosphere, mechanical pre-cleaning to reduce oxide scale thickness by 30.0%, a first pickling aqueous solution with 8.00 wt% hydrogen fluoride content, a pickling temperature of 15℃, a pickling pH of 2.0, a pickling time of 0.5 min, post-pickling cleaning to pH 6 and drying at 60℃ for 5 min, a nitric acid content of 10.00 wt%, a passivation temperature of 15℃, a passivation pH of 2.0, a passivation time of 1.0 min, post-passivation cleaning to pH 6 and drying at 60℃ for 5 min.
[0078] Comparative Example 2: Basically the same as Example 1, except that the cross-sectional reduction rate of the final small deformation cold finishing is 8.00%, while other conditions remain at UNS. The N04400 nickel-copper alloy matrix contains 28.00 wt% copper, 0.20 wt% manganese, 2.50 wt% iron, 0.02 wt% silicon, 0.005 wt% carbon, 0.0005 wt% sulfur, 0.3045 wt% unavoidable impurities, and nickel as the balance. The finished product has an outer diameter of 6.0 mm, a wall thickness of 0.50 mm, a total cross-sectional reduction rate of 35.00%, a single-pass cross-sectional reduction rate of 8.00%, annealing at 760℃ for 60 min in a nitrogen atmosphere, mechanical pre-cleaning to reduce oxide scale thickness by 30.0%, a first pickling aqueous solution with 8.00 wt% hydrogen fluoride content, a pickling temperature of 15℃, a pickling pH of 2.0, a pickling time of 0.5 min, post-pickling cleaning to pH 6 and drying at 60℃ for 5 min, a nitric acid content of 10.00 wt%, a passivation temperature of 15℃, a passivation pH of 2.0, a passivation time of 1.0 min, post-passivation cleaning to pH 6 and drying at 60℃ for 5 min.
[0079] Comparative Example 3: Essentially the same as Example 1, except that the annealing temperature was 720℃, and other conditions were maintained as follows: UNSN04400 nickel-copper alloy matrix containing 28.00 wt% copper, 0.20 wt% manganese, 2.50 wt% iron, 0.02 wt% silicon, 0.005 wt% carbon, 0.0005 wt% sulfur, 0.3045 wt% unavoidable impurities, and nickel as the balance; finished product outer diameter 6.0 mm, wall thickness 0.50 mm, total cross-sectional reduction rate 35.00%, single-pass cross-sectional reduction rate 8.00%, annealed in a nitrogen atmosphere. The process included: heat preservation for 60 min, final small deformation cold straightening section reduction rate of 2.00%, mechanical pre-cleaning oxide scale thickness reduction of 30.0%, first pickling aqueous solution with hydrogen fluoride content of 8.00 wt%, pickling temperature of 15℃, pickling pH of 2.0, pickling time of 0.5 min, post-pickling cleaning to pH of 6 and drying at 60℃ for 5 min, nitric acid content of 10.00 wt%, passivation temperature of 15℃, passivation pH of 2.0, passivation time of 1.0 min, post-passivation cleaning to pH of 6 and drying at 60℃ for 5 min.
[0080] Comparative Example 4: Essentially the same as Example 1, except the annealing temperature was 920℃, and other conditions were maintained as follows: UNSN04400 nickel-copper alloy matrix containing 28.00 wt% copper, 0.20 wt% manganese, 2.50 wt% iron, 0.02 wt% silicon, 0.005 wt% carbon, 0.0005 wt% sulfur, 0.3045 wt% unavoidable impurities, and nickel as the balance; finished product outer diameter 6.0 mm, wall thickness 0.50 mm, total cross-sectional reduction rate 35.00%, single-pass cross-sectional reduction rate 8.00%, annealed in a nitrogen atmosphere. The process included: heat preservation for 60 min, final small deformation cold straightening section reduction rate of 2.00%, mechanical pre-cleaning oxide scale thickness reduction of 30.0%, first pickling aqueous solution with hydrogen fluoride content of 8.00 wt%, pickling temperature of 15℃, pickling pH of 2.0, pickling time of 0.5 min, post-pickling cleaning to pH of 6 and drying at 60℃ for 5 min, nitric acid content of 10.00 wt%, passivation temperature of 15℃, passivation pH of 2.0, passivation time of 1.0 min, post-passivation cleaning to pH of 6 and drying at 60℃ for 5 min.
[0081] Comparative Example 5: Essentially the same as Example 1, except that the pickling time was 0.2 min, and other conditions were maintained as follows: UNSN04400 nickel-copper alloy matrix with copper 28.00 wt%, manganese 0.20 wt%, iron 2.50 wt%, silicon 0.02 wt%, carbon 0.005 wt%, sulfur 0.0005 wt%, unavoidable impurities 0.3045 wt%, and nickel as the balance; finished product outer diameter 6.0 mm, wall thickness 0.50 mm, total cross-sectional reduction rate 35.00%, and single-pass cross-sectional reduction rate 8.00%. Annealing at 760℃ for 60 min in nitrogen atmosphere; final pass small deformation cold straightening section reduction rate of 2.00%; mechanical pre-cleaning oxide scale thickness reduction ratio of 30.0%; first pickling aqueous solution with hydrogen fluoride content of 8.00wt%; pickling temperature of 15℃; pickling pH of 2.0; post-pickling cleaning to pH of 6 and drying at 60℃ for 5 min; nitric acid content of 10.00wt%; passivation temperature of 15℃; passivation pH of 2.0; passivation time of 1.0 min; post-passivation cleaning to pH of 6 and drying at 60℃ for 5 min.
[0082] Comparative Example 6: Essentially the same as Example 1, except that the pickling time was 20.0 min, and other conditions were maintained as follows: UNSN04400 nickel-copper alloy matrix with copper 28.00 wt%, manganese 0.20 wt%, iron 2.50 wt%, silicon 0.02 wt%, carbon 0.005 wt%, sulfur 0.0005 wt%, unavoidable impurities 0.3045 wt%, and nickel as the balance; finished product outer diameter 6.0 mm, wall thickness 0.50 mm, total cross-sectional reduction rate 35.00%, and single-pass cross-sectional reduction rate 8.00%. Annealing at 760℃ for 60 min in nitrogen atmosphere; final pass small deformation cold straightening section reduction rate of 2.00%; mechanical pre-cleaning oxide scale thickness reduction ratio of 30.0%; first pickling aqueous solution with hydrogen fluoride content of 8.00wt%; pickling temperature of 15℃; pickling pH of 2.0; post-pickling cleaning to pH of 6 and drying at 60℃ for 5 min; nitric acid content of 10.00wt%; passivation temperature of 15℃; passivation pH of 2.0; passivation time of 1.0 min; post-passivation cleaning to pH of 6 and drying at 60℃ for 5 min.
[0083] Comparative Example 7: Basically the same as Example 1, except that no mechanical pre-cleaning was performed, the oxide scale thickness reduction rate was 0%, and other conditions were kept at UNS. The N04400 nickel-copper alloy matrix contains 28.00 wt% copper, 0.20 wt% manganese, 2.50 wt% iron, 0.02 wt% silicon, 0.005 wt% carbon, 0.0005 wt% sulfur, 0.3045 wt% unavoidable impurities, and nickel as the balance. The finished product has an outer diameter of 6.0 mm, a wall thickness of 0.50 mm, a total cross-sectional reduction rate of 35.00%, a single-pass cross-sectional reduction rate of 8.00%, annealing at 760℃ in a nitrogen atmosphere for 60 min, a final pass small deformation cold finishing cross-sectional reduction rate of 2.00%, a first pickling aqueous solution with a hydrogen fluoride content of 8.00 wt%, a pickling temperature of 15℃, a pickling pH of 2.0, a pickling time of 0.5 min, post-pickling cleaning to pH 6 and drying at 60℃ for 5 min, a nitric acid content of 10.00 wt%, a passivation temperature of 15℃, a passivation pH of 2.0, a passivation time of 1.0 min, post-passivation cleaning to pH 6 and drying at 60℃ for 5 min.
[0084] Comparative Example 8: Essentially the same as Example 1, except that the nitric acid content in the nitric acid aqueous solution was 5.00 wt%, and other conditions were maintained as follows: UNS N04400 nickel-copper alloy matrix, copper 28.00 wt%, manganese 0.20 wt%, iron 2.50 wt%, silicon 0.02 wt%, carbon 0.005 wt%, sulfur 0.0005 wt%, unavoidable impurities 0.3045 wt%, nickel as the balance; finished product outer diameter 6.0 mm, wall thickness 0.50 mm, total cross-sectional reduction rate 35.00%, single-pass cross-sectional reduction rate 8.00%, annealing at 760°C in a nitrogen atmosphere for 60 min, final pass... Small deformation cold straightening section reduction rate 2.00%, mechanical pre-cleaning oxide scale thickness reduction ratio 30.0%, first pickling aqueous solution hydrogen fluoride content 8.00wt%, pickling temperature 15℃, pickling pH 2.0, pickling time 0.5min, after pickling, cleaning to pH 6 and drying at 60℃ for 5min, passivation temperature 15℃, passivation pH 2.0, passivation time 1.0min, after passivation, cleaning to pH 6 and drying at 60℃ for 5min.
[0085] Comparative Example 9: Basically the same as Example 1, except that no final small deformation cold straightening is performed after annealing, the cross-sectional reduction rate is 0%, and other conditions are kept at UNS. The N04400 nickel-copper alloy matrix contains 28.00 wt% copper, 0.20 wt% manganese, 2.50 wt% iron, 0.02 wt% silicon, 0.005 wt% carbon, 0.0005 wt% sulfur, 0.3045 wt% unavoidable impurities, and nickel as the balance. The finished product has an outer diameter of 6.0 mm, a wall thickness of 0.50 mm, a total cross-sectional reduction rate of 35.00%, a single-pass cross-sectional reduction rate of 8.00%, annealing at 760℃ for 60 min in a nitrogen atmosphere, mechanical pre-cleaning to reduce oxide scale thickness by 30.0%, a first pickling aqueous solution with 8.00 wt% hydrogen fluoride content, a pickling temperature of 15℃, a pickling pH of 2.0, a pickling time of 0.5 min, post-pickling cleaning to pH 6 and drying at 60℃ for 5 min, a nitric acid content of 10.00 wt%, a passivation temperature of 15℃, a passivation pH of 2.0, a passivation time of 1.0 min, post-passivation cleaning to pH 6 and drying at 60℃ for 5 min. This comparative example is used to examine the synergistic relationship between recrystallization annealing and final pass small deformation cold finishing.
[0086] Comparative Example 10: Basically the same as Example 1, except that Cu / Ni ratio controlled pickling was not performed, and nitric acid passivation was performed directly after annealing and mechanical pre-cleaning, while other conditions were kept at UNS. The N04400 nickel-copper alloy matrix contains 28.00 wt% copper, 0.20 wt% manganese, 2.50 wt% iron, 0.02 wt% silicon, 0.005 wt% carbon, 0.0005 wt% sulfur, 0.3045 wt% unavoidable impurities, and nickel as the balance. The finished product has an outer diameter of 6.0 mm, a wall thickness of 0.50 mm, a total cross-sectional reduction rate of 35.00%, a single-pass cross-sectional reduction rate of 8.00%, annealing at 760℃ for 60 min in a nitrogen atmosphere, a final pass of small deformation cold finishing resulting in a cross-sectional reduction rate of 2.00%, a 30.0% reduction in oxide scale thickness due to mechanical pre-cleaning, a nitric acid content of 10.00 wt%, a passivation temperature of 15℃, a passivation pH of 2.0, a passivation time of 1.0 min, and post-passivation cleaning to a pH of 6 followed by drying at 60℃ for 5 min. This comparative example is used to investigate the synergistic relationship between pickling and nitric acid passivation controlled by the Cu / Ni ratio.
[0087] Comparative Example 11: Basically the same as Example 1, except that after Cu / Ni ratio controlled pickling, cleaning and drying, nitric acid passivation was not performed, and other conditions were kept at UNS. The N04400 nickel-copper alloy matrix contains 28.00 wt% copper, 0.20 wt% manganese, 2.50 wt% iron, 0.02 wt% silicon, 0.005 wt% carbon, 0.0005 wt% sulfur, 0.3045 wt% unavoidable impurities, and nickel as the balance. The finished product has an outer diameter of 6.0 mm, a wall thickness of 0.50 mm, a total cross-sectional reduction rate of 35.00%, a single-pass cross-sectional reduction rate of 8.00%, annealing at 760℃ for 60 min in a nitrogen atmosphere, a final pass with small deformation cold finishing resulting in a cross-sectional reduction rate of 2.00%, a mechanical pre-cleaning oxide scale thickness reduction rate of 30.0%, a first pickling aqueous solution with a hydrogen fluoride content of 8.00 wt%, a pickling temperature of 15℃, a pickling pH of 2.0, a pickling time of 0.5 min, and post-pickling cleaning to a pH of 6 followed by drying at 60℃ for 5 min. This comparative example is used to investigate the synergistic relationship between pickling and nitric acid passivation controlled by the Cu / Ni ratio.
[0088] Characterization and performance testing: Chemical composition analysis was conducted on the final state tubing of Examples 1–4 and all comparative examples to confirm whether the nickel, copper, manganese, iron, silicon, carbon, sulfur, and unavoidable impurities in the UNSN04400 nickel-copper alloy matrix were consistent with the design composition. Nickel, copper, manganese, iron, and silicon were determined using ICP-OES, with samples taken from the middle of the tubing wall and acid-dissolved. Carbon and sulfur were determined using combustion infrared spectroscopy, with n≥3 for each batch. Data fields included the mean and standard deviation of Ni, Cu, Mn, Fe, Si, C, S, and unavoidable impurities, in wt%, which were entered into the composition record field of the performance comparison summary table.
[0089] Room temperature tensile and hardness tests were conducted on longitudinal specimens taken from the final state of the tubing to evaluate the balance between plasticity and strength after annealing and the final small deformation. Tensile tests were performed according to GB / T228.1-2021 "Metallic materials, tensile testing—Part 1: Tests at room temperature," with a gauge length L0 of 50 mm, and Rm, Rp0.2, and A were recorded. Rockwell hardness tests were performed according to GB / T230.1-2018, using the HRB scale, with n≥3 per group.
[0090] Grain size testing was conducted on the final state pipe wall cross-section to evaluate the control effect of recrystallization annealing and final minor deformation on the microstructure. Samples were observed after mounting, polishing, and adaptive etching. The average grain size grade was assessed according to GB / T6394-2017 "Method for Determination of Average Grain Size of Metals". At least three cross-sections were selected for each batch, and at least five fields of view were statistically analyzed for each cross-section.
[0091] The surface Cu retention index R experiment was conducted on pipes in their final state after pickling, passivation, cleaning, and drying. The aim was to quantify the degree to which the Cu / Ni atomic ratio on the inner and outer surfaces was retained relative to the Cu / Ni atomic ratio in the matrix. The surface Cu / Ni atomic ratio was determined using XPS according to the general rules for XPS analysis in GB / T19500-2025, with the energy scale calibrated according to GB / T22571-2017. The matrix Cu / Ni atomic ratio was measured using ICP-OES on samples from the middle of the pipe wall.
[0092] The surface roughness, oxide scale residual area ratio, and pickling weight loss experiments were conducted on pipes before and after pickling and passivation to evaluate the relationship between surface treatment intensity and surface quality. The outer surface roughness Ra was measured according to the profile method parameters specified in GB / T1031-2009, with at least five measurement lines taken along the axial direction. The oxide scale residual area ratio was calculated by binarizing the inner and outer surface images. Within the same batch of tests, the image acquisition light source, acquisition magnification, exposure conditions, and grayscale binarization threshold rules for the oxide scale area remained consistent. The pickling weight loss was calculated by dividing the difference in drying quality before and after pickling by the sum of the inner and outer surface areas.
[0093] The flaring and flattening tests are conducted on the end and short section specimens of the final-state pipe material. The purpose is to evaluate the suitability of the forming process and whether cracks and delamination occur at the bending points. The flaring test is performed according to GB / T242-2007 "Test Method for Flaring of Metallic Pipes", using a 60° cone mandrel and calculating the flaring ratio. The flattening test is performed according to GB / T246-2017 "Test Method for Flattening of Metallic Pipes", and the appearance of the bending points is recorded.
[0094] The intra-batch stability and surface Cu / Ni atomic ratio stability experiments under humid heat conditions were conducted on tubing from the same heat number, annealing batch, final small deformation cold working batch, and pickling / passivation batch. The aim was to evaluate intra-batch consistency and the ability to retain passivated surfaces. At least five tubing samples were randomly selected from each batch, and A, R, and Ra were measured and their coefficients of variation were calculated. Additional samples were placed at 40℃ and 90% relative humidity for 72 hours, and R and Ra were measured again. Data fields included the coefficient of variation for A, R, and Ra, the rate of change of R after humid heat, and the rate of change of Ra after humid heat. The rate of change of R after humid heat was calculated based on the relative change of R value on the same surface before and after humid heat treatment.
[0095] Figure 1 This diagram illustrates the effect of the reduction rate of the final small deformation cold straightening section on the elongation after fracture (A) and the surface Cu retention index (R) of the outer surface in this scheme. Figure 2 The figures above illustrate the effect of annealing temperature on the elongation after fracture (A) and the surface Cu retention index (R) of the outer surface. These two figures are used to explain the coupling relationship between microstructure control parameters and surface element retention. Figure 1 Based on the process of Example 1, only the shrinkage rate of the final small deformation cold-forming section was adjusted to 1.00%, 2.00%, 3.00%, 4.00%, 5.00%, 6.00%, and 7.00%, while the remaining annealing, pickling, passivation, and cleaning conditions remained the same. The results show that when the shrinkage rate is between approximately 3.00% and 5.00%, the elongation after fracture (A) and the surface Cu retention index (R) of the outer surface of the pipe are both at optimal levels. If the shrinkage rate is too low, the dimensional correction and surface deformation adjustment effects are insufficient; if the shrinkage rate is too high, excessive deformation energy storage is easily introduced, affecting the stability of subsequent surface treatments. Figure 2 Based on the process of Example 1, only the annealing temperature was adjusted to 720℃, 760℃, 790℃, 820℃, 850℃, 880℃, and 920℃, while the other cold straightening, pickling, and passivation parameters remained the same. The results showed that when the annealing temperature was around 820℃, the elongation after fracture (A) and the outer surface (R) could be well balanced, indicating that moderate recrystallization annealing is beneficial to grain homogenization and plasticity recovery, and can also reduce the fluctuation of the surface Cu retention state during subsequent pickling and passivation processes.
[0096] Figure 3 This diagram illustrates the effect of pickling time on the Cu retention index R on the outer surface and the ratio of residual oxide scale area in this scheme. Figure 4 This diagram illustrates the effect of nitric acid content on the surface Cu retention index R (outer surface) and the rate of change of R after humidification. Figure 5 The above three figures illustrate the effect of the mechanical pre-cleaning ratio on the Cu retention index R and surface roughness Ra of the surface. These figures further demonstrate that the surface treatment intensity needs to match the preceding microstructure. Figure 3Based on the process in Example 1, only the pickling time was adjusted to 0.2 min, 0.5 min, 4.0 min, 8.0 min, 12.0 min, 15.0 min, and 20.0 min, while the acid composition, temperature, and pretreatment conditions remained consistent. The results showed that when the pickling time was too short, the residual oxide scale area was too high, making it difficult to obtain a clean surface; when the pickling time was too long, the outer surface area (R) decreased significantly, indicating that excessive pickling would exacerbate surface Cu loss or surface disturbance. Therefore, short-duration, controlled Cu / Ni ratio pickling is more conducive to simultaneously achieving descaling and Cu / Ni atomic ratio control. Figure 4 Based on the process of Example 1, only the nitric acid content was adjusted to 5.0 wt%, 10.0 wt%, 14.0 wt%, 18.0 wt%, 22.0 wt%, 25.0 wt%, and 30.0 wt%, while the pickling time, temperature, and cleaning conditions remained the same. The results showed that when the nitric acid content was in the middle range, the outer surface area of R was higher and the rate of change of R after wet heating was lower, indicating that moderate nitric acid passivation can improve the surface stability, while insufficient or excessive passivation strength is not conducive to stabilizing the Cu / Ni surface ratio. Figure 5 Based on the process of Example 1, only the reduction ratio of oxide scale thickness caused by mechanical pre-cleaning was adjusted to 10.0%, 30.0%, 45.0%, 60.0%, 75.0%, 90.0%, and 95.0%, while the remaining annealing, pickling, and passivation parameters remained the same. The results show that insufficient pre-cleaning leads to excessive pickling load and increased roughness, while excessive pre-cleaning may cause surface damage or local activation. A moderate mechanical pre-cleaning ratio is beneficial to improving pickling uniformity, thereby balancing the R outer surface and Ra control. Figure 5 This reflects the relative trend of the change in the mechanical pre-cleaning ratio under the baseline conditions of Example 1.
[0097] Figure 6 The graphs show the grain size difference distribution of Example 1, Comparative Example 1, and Comparative Example 2. Figure 7 The graph shows the cumulative grain size distribution of Example 1, Comparative Example 1, and Comparative Example 2. Figure 8 The above three figures show the EBSD orientation difference distribution curves for Example 1, Comparative Example 1, and Comparative Example 2. These three figures verify, from a microstructural perspective, the effect of matching the recrystallization annealing sequence with the final minor deformation sequence. Figure 6 In Example 1, the grain size difference distribution is more concentrated, and the tails of coarse grains are significantly reduced, indicating that its microstructure uniformity is better than that of the comparative example. Figure 7 In Example 1, the cumulative grain size distribution curve transitions more smoothly and the distribution range is narrower, further indicating that the grain size dispersion is lower, which is beneficial to reducing local deformation unevenness. Figure 8In Example 1, the EBSD orientation difference distribution is more reasonable, and the ratio of low-angle orientation difference to high-angle orientation difference is more balanced, indicating that the pipe retains a moderate deformation adjustment effect after recrystallization softening. Therefore, this solution does not simply increase the degree of annealing softening, but rather achieves synergistic effects in plasticity recovery, microstructure uniformity, and adaptability to subsequent surface treatments through continuous control of annealing and small deformation.
[0098] Figure 9 The figures show the room temperature engineering stress-strain curves for Example 1, Comparative Example 1, and Comparative Example 9. Figure 10 The above two graphs are scatter plots showing the mean and standard deviation of the flaring rate for Example 1, Comparative Example 1, and Comparative Example 9. These graphs are used to evaluate the macroscopic forming properties of the pipes after microstructure regulation. Figure 9 The results show that Example 1, while maintaining a high strength level, has a longer uniform deformation stage and higher elongation after fracture, indicating that it does not sacrifice overall plasticity due to surface treatment or small deformation control. Figure 10 The results show that the average flaring rate of Example 1 was 15.0%, higher than that of Comparative Example 1 and Comparative Example 9, and the data dispersion was low, indicating that the deformation of the pipe end flaring process in Example 1 was more stable. This result is consistent with... Figures 6 to 8 Corresponding to the organizational characterization, it is shown that a uniform grain structure and a moderate orientation difference distribution can effectively improve the forming consistency in subsequent processing such as flaring and joining.
[0099] Figure 11 The above are the XPS Cu2p / Ni2p peak superposition spectra of Example 1, Comparative Example 10, and Comparative Example 11. Figure 12 The figures above show a comparison of the Cu retention index R of the outer surfaces of Examples 1, 10, and 11. These figures illustrate the effect of Cu / Ni ratio control on the Cu / Ni state of the outer surfaces through pickling and nitric acid passivation. Figure 11 In Example 1, the Cu-related peak intensity and Ni-related peak intensity match more stably, indicating that its outer surface can still maintain a reasonable Cu / Ni element ratio after pickling and passivation. In contrast, Comparative Examples 10 and 11 show significant deviations in surface element state due to insufficient control of Cu / Ni ratio pickling or passivation conditions. Figure 12 In Example 1, the R-value of the outer surface area was 0.80, which was higher than that of Comparative Examples 10 and 11. This indicates that the proposed method can reduce the risk of deviation in the surface Cu / Ni ratio and achieve a balance between the acid pickling cleaning effect and the control of the Cu / Ni atomic ratio. This result directly addresses the problem that the surface Cu retention state of nickel-copper alloy pipes is easily reduced during surface strengthening treatment.
[0100] Figure 13 This is a dual Y-axis graph showing the change rate of surface roughness Ra versus R after humid heat for Examples 1, 6, and 8. Figure 14The figures show the ratio of residual oxide scale area to pickling weight loss in Examples 1, 5, and 7, plotted on a dual Y-axis. These figures further verify the combined effect of surface quality and surface Cu / Ni atomic ratio stability under humid and hot conditions. Figure 13 The results show that the surface roughness Ra of Example 1 is 1.60 μm, and the change rate of R after humid heat is 6.8%, both of which are at a low level. This indicates that Example 1 not only has a relatively smooth surface, but also maintains a relatively stable Cu / Ni ratio after being exposed to humid heat. Figure 14 The results show that Example 1 exhibits a low residual oxide scale area, while the pickling weight loss remains at a moderate level. This indicates that the combination of mechanical pre-cleaning and Cu / Ni ratio-controlled pickling effectively removes oxide scale while avoiding excessive corrosion. Therefore, this solution addresses the challenge of simultaneously achieving oxide scale removal, roughness reduction, and surface stability by controlling mechanical pre-cleaning, pickling time, and nitric acid passivation intensity.
[0101] Figure 15 The images show a comparison of the SEM morphology of the final product from Example 1 and the final product from Comparative Example 6, used to further illustrate the influence of short-term Cu / Ni ratio controlled pickling on the surface quality of UNS N04400 nickel-copper alloy seamless tubing from a microscopic surface morphology perspective. Figure 15 In Figure 'a', the final product of Example 1 is a magnified SEM image. The sample was obtained after nitrogen annealing at 760℃ for 60 min, cold straightening with 2.00% final small deformation, mechanical pre-cleaning, pickling with Cu / Ni ratio control for 0.5 min, and passivation with 10.00wt% nitric acid. The results show that after the oxide scale residual area ratio was reduced to 2.0%, the surface still maintained good continuity. Figure 15 Figure b shows a magnified SEM image of the final product of Comparative Example 6. Its alloy system and pipe specifications are the same as in Example 1, but the pickling time was extended to 20.0 min. The results show more obvious surface roughening, grain boundary etching, or corrosion texture, indicating that prolonged pickling destroys surface uniformity. Furthermore, Figure 15 c in the image is a high-magnification SEM image of the final product of Example 1. Micron-level peaks and valleys, slight pickling texture, and low residual oxide scale characteristics corresponding to Ra of 1.60 μm can be observed, indicating that the pickling intensity of Example 1 is under control. Figure 15 In the image, d is a high-magnification SEM image of the final product of Comparative Example 6. Micro-pits, grooves, or corrosion product residues formed under the pickling conditions can be observed, further indicating that short-term Cu / Ni ratio pickling for 0.5 min is more conducive to suppressing surface damage.
[0102] Figure 16 The TEM structure comparison images of the final product of Example 1 and the final product of Comparative Example 6 are used to verify the rationality of the surface treatment process in terms of near-surface structure, passivation film continuity, and the preservation of the matrix crystal structure. Figure 16 In Figure 'a', the image is a bright-field TEM image of the final product of Example 1. The object of observation is the interface between the surface film and the Ni-Cu alloy substrate after pickling and passivation with controlled Cu / Ni ratio for 0.5 min. The results show that the near-surface structure is continuous and no obvious corrosion holes or interface delamination are observed. Figure 16 b in the figure is the bright-field TEM image of the final product of Comparative Example 6. The objects of observation are the surface layer and near-surface substrate formed after pickling for 20.0 min and then passivation. The results show that the interface undulation, non-uniform corrosion product layer or local micropores are more obvious, indicating that excessive pickling will weaken the integrity of the near-surface layer. Figure 16 c in the image is the HRTEM image of the final product of Example 1, which shows that the Ni-Cu face-centered cubic solid solution lattice fringes in the UNS N04400 nickel-copper alloy matrix are clear, indicating that the surface treatment in Example 1 did not destroy the matrix crystal structure. Figure 16 In the image, d is the HRTEM image of the final product of Comparative Example 6, which shows an increase in local disordered layers, lattice distortion, or corrosion product crystalline regions near the surface, indicating that excessive acid washing reduces the stability of the surface interface structure. Figure 16 In the figure, e is the EDS surface scan of the final product of Example 1. Qualitatively, it shows that elements such as Ni, Cu, and O are relatively uniformly distributed in the near-surface layer. The quantitative result of the surface Cu retention index R is based on the Cu / Ni atomic ratio measured by XPS and the matrix Cu / Ni atomic ratio measured by ICP-OES. Figure 16 f in the diagram is the EDS surface scan of the final product of Comparative Example 6, showing uneven elemental distribution or a more complex surface reaction layer after prolonged acid washing. Combined with... Figure 15 and Figure 16 It can be seen that Example 1 achieves simultaneous improvement in high plasticity, low roughness, stable Cu / Ni atomic ratio control, and hygrothermal stability by matching the order of recrystallization annealing, final small deformation, mechanical pre-cleaning, short-time Cu / Ni ratio control pickling, and nitric acid passivation. This effectively solves the contradiction between plasticity control and surface stabilization treatment in UNS N04400 nickel-copper alloy tubing.
[0103] Table 1 Performance of Examples and Comparative Examples As can be seen from the performance of the examples and comparative examples in Table 1, Examples 1–4 show a relatively stable overall trend in terms of elongation after fracture, flaring rate, surface Cu retention index, roughness, and R change rate after wet heating. The conventional comparative examples, due to deviations in final small deformation, annealing temperature, pickling time, mechanical pre-cleaning, or nitric acid content, exhibit trends such as decreased plasticity, increased roughness, increased oxide scale residue, or insufficient control of the surface Cu / Ni atomic ratio. In the synergistic comparative examples, the relevant indicators deteriorated synchronously after the absence of final small deformation, Cu / Ni ratio control during pickling, or nitric acid passivation. This indicates that the combination of annealing small deformation and the order of pickling and passivation help to balance mutually restrictive performance characteristics.
[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A high-ductility nickel-based alloy pipe, characterized in that, The tubing is a seamless UNS N04400 nickel-copper alloy tubing, comprising a UNS N04400 nickel-copper alloy matrix and a surface Cu / Ni atomic ratio controlled structure located on the inner and outer surfaces of the UNS N04400 nickel-copper alloy matrix. The controlled Cu / Ni atomic ratio structure satisfies a Cu retention index R of 0.80-1.20 on both the inner and outer surfaces. The Cu retention index R is defined as the ratio of the Cu / Ni atomic ratio on the pipe surface to the Cu / Ni atomic ratio in the pipe matrix. The Cu / Ni atomic ratio on the pipe surface is determined by X-ray photoelectron spectroscopy according to GB / T19500-2025, and the energy scale is calibrated according to GB / T22571-2017. The Cu / Ni atomic ratio in the pipe matrix is determined by inductively coupled plasma atomic emission spectrometry. The average grain size of the pipe is grade 6-8, and the average grain size is measured at the pipe wall section in the final state according to GB / T6394-2017. The room temperature elongation after fracture A is 45.0-55.0%, and the room temperature elongation after fracture A is measured at the sample with a gauge length L0 of 50 mm according to GB / T228.1-2021. The outer surface roughness Ra is 0.20-1.60 μm, and the outer surface roughness Ra is measured along the axial direction on the outer surface of the pipe in the final state according to GB / T1031-2009. The flaring ratio is 15.0-25.0%, and the flaring ratio is measured using a conical core with a cone angle of 60° according to GB / T242-2007.
2. The high-ductility nickel-based alloy pipe according to claim 1, characterized in that, Based on a total pipe mass of 100 wt%, the UNS N04400 nickel-copper alloy matrix comprises: nickel, the balance after deducting copper, manganese, iron, silicon, carbon, sulfur, and unavoidable impurities, with a content of 63.00-69.00 wt%; copper, with a content of 28.00-34.00 wt%; manganese, with a content of 0.20-2.00 wt%; iron, with a content of 0.10-2.50 wt%; silicon, with a content of 0.02-0.50 wt%; carbon, with a content of 0.005-0.300 wt%; sulfur, with a content of 0.0005-0.024 wt%; and unavoidable impurities totaling no more than 0.50 wt%, and the sum of all components being 100 wt%.
3. The high-ductility nickel-based alloy pipe according to claim 1, characterized in that, The surface Cu / Ni atomic ratio controlled structure is formed through a Cu / Ni ratio controlled acid pickling step, which includes the following steps: A1. Provide the annealed seamless tubing of the UNS N04400 nickel-copper alloy; A2. Prepare an acid pickling solution, wherein the acid pickling solution is selected from any one of a first acid pickling solution, a second acid pickling solution, and a third acid pickling solution, wherein the first acid pickling solution is prepared by hydrofluoric acid and deionized water, and the hydrogen fluoride content is 8.00-30.00 wt%; the second acid pickling solution is prepared by hydrochloric acid, copper sulfate pentahydrate, and deionized water, and the hydrogen chloride content is 5.00-15.00 wt%, and the copper sulfate pentahydrate content is 20-100 g / L; the third acid pickling solution is prepared by sulfuric acid, copper sulfate pentahydrate, and deionized water, and the sulfuric acid content is 8.00-20.00 wt%, and the copper sulfate pentahydrate content is 20-100 g / L; A3. Place the pipe in the pickling solution and treat it for 0.5-15.0 min under normal pressure, temperature of 15-40℃, and pH value not higher than 2; A4. Pickling shall be terminated when the residual oxide scale area on the surface of the pipe is 0-2.0% and the pickling weight loss is 0.20-3.00 g / m². A5. Rinse with deionized water until the pH of the final rinse water is 6-8, and dry at 60-120℃ for 5-30 minutes; A6. The surface Cu retention index R of the obtained pipe is 0.80-1.
20.
4. The high-ductility nickel-based alloy pipe according to claim 3, characterized in that, The controlled Cu / Ni atomic ratio structure on the surface is further formed through a nitric acid passivation step, which includes the following steps: B1. The pipe material treated by the Cu / Ni ratio controlled pickling step is placed in a nitric acid aqueous solution, wherein the nitric acid aqueous solution is prepared by mixing nitric acid and deionized water, and the nitric acid content is 10.00-25.00 wt%. B2. Passivate for 1.0-15.0 min under normal pressure, temperature of 15-40℃, and pH value not higher than 2; B3. Rinse with deionized water until the pH of the final rinse water is 6-8; B4. Dry at 60-120℃ for 5-30 minutes; B5. The surface roughness Ra of the resulting pipe is 0.20-1.60 μm, and the surface Cu retention index R is 0.80-1.
20.
5. The high-ductility nickel-based alloy pipe according to claim 1, characterized in that, The UNS N04400 nickel-copper alloy matrix is formed by recrystallization annealing and final minor deformation cold working, specifically including: C1. Anneal the cold-worked UNS N04400 nickel-copper alloy tubing at a temperature of 760-880℃ and a holding time of 10-60 minutes. C2. The annealing is carried out in a nitrogen or argon atmosphere, or the annealing is carried out in an air atmosphere followed by pickling with Cu / Ni ratio control. C3. After annealing, perform final minor deformation cold drawing or cold straightening, wherein the cross-sectional reduction rate of the final minor deformation cold drawing or cold straightening is 2.00-6.00%; C4. After the final small deformation cold drawing or cold straightening, the average grain size of the obtained pipe is grade 6-8, and the room temperature elongation after fracture A is 45.0-55.0%.
6. The high-ductility nickel-based alloy pipe according to claim 1, characterized in that, The outer diameter of the pipe is 6.0-168.0 mm, the wall thickness is 0.50-12.00 mm, the ellipticity is 0-1.50%, the wall thickness deviation is 0-10.00%, and there are no visible cracks, folds, or delaminations on the inner and outer surfaces. Furthermore, after the pipe undergoes a flattening test according to GB / T246-2017, there are no cracks or delaminations at the bent parts.
7. The high-ductility nickel-based alloy pipe according to claim 1, characterized in that, The tubing has a room temperature tensile strength Rm of 520-580 MPa, a specified plastic elongation strength Rp0.2 of 280-350 MPa, and a Rockwell hardness HRB of 75-85.
8. The high-ductility nickel-based alloy pipe according to claim 1, characterized in that, In the aforementioned tubing, the inter-batch or intra-batch coefficient of variation for elongation at break A is 0-8.0%, the intra-batch coefficient of variation for surface Cu retention index R is 0-10.0%, and the intra-batch coefficient of variation for external surface roughness Ra is 0-15.0%.
9. A method for preparing a high-ductility nickel-based alloy pipe as described in any one of claims 1-8, characterized in that, Includes the following steps: S1. Provide UNS N04400 nickel-copper alloy tube blanks; S2. The UNS N04400 nickel-copper alloy tube blank is cold rolled and / or cold drawn to form a cold-worked tube; S3. Anneal the cold-worked pipe at a temperature of 760-880℃ and a holding time of 10-60 minutes. S4. Perform final small-deformation cold drawing or cold straightening on the annealed pipe, with a cross-sectional reduction rate of 2.00-6.00%; S5. After mechanical pre-cleaning of the pipe material treated in step S4, pickling with a Cu / Ni ratio controlled by any one of the following pickling solutions: hydrofluoric acid aqueous solution, hydrochloric acid-copper sulfate pentahydrate aqueous solution, and sulfuric acid-copper sulfate pentahydrate aqueous solution. The pickling is carried out at normal pressure, temperature of 15-40℃, and pH value not higher than 2 for 0.5-15.0 min to remove oxide scale and form a surface Cu / Ni atomic ratio controlled structure. S6. The pipe treated in step S5 is passivated with a nitric acid aqueous solution with a nitric acid content of 10.00-25.00wt% to form a passivated surface; S7. Clean, dry, straighten and cut to length to obtain the high-plasticity nickel-based alloy pipe.
10. The preparation method according to claim 9, characterized in that, In step S2, the total cross-sectional reduction rate of the cold rolling and / or cold drawing is 35.00-75.00%, and the single-pass cross-sectional reduction rate is 8.00-30.00%; in step S4, the final pass of small deformation cold drawing or cold sizing is not subjected to recrystallization annealing at a temperature higher than 700°C.
Citation Information
Patent Citations
Manufacturing method of small-caliber nickel-copper alloy seamless heat exchange tube
CN119387343A
A method for manufacturing thin-walled, ultra-long nickel-copper alloy tubing
CN102294579A
Process for manufacturing small-bore nickel base alloy seamless square tubes
CN103317305A